A protocol for use of medetomidine anesthesia in rats for extended studies using task-induced BOLD contrast and resting-state functional connectivity - Pawela, Christopher P. (2009)
The α2-adrenoreceptor agonist, medetomidine, which exhibits dose-dependent sedative effects and is gaining acceptance in small-animal functional magnetic resonance imaging (fMRI), has been studied. Rats were examined on the bench using the classic tail-pinch method with three infusion sequences: 100 μg/kg/hr, 300 μg/kg/hr, or 100 μg/kg/hr followed by 300 μg/kg/hr. Stepping the infusion rate from 100 to 300 μg/kg/hr after 2.5 hours resulted in a prolonged period of approximately level sedation that cannot be achieved by a constant infusion of either 100 or 300 μg/kg/hr. By stepping the infusion dosage, experiments as long as six hours are possible. Functional MRI experiments were carried out on rats using a frequency dependent electrical stimulation protocol—namely, forepaw stimulation at 3, 5, 7, and 10 Hz. Each rat was studied for a four-hour period, divided into two equal portions. During the first portion, rats were started at a 100 μg/kg/hr constant infusion. During the second portion, four secondary levels of infusion were used: 100, 150, 200, and 300 μg/kg/hr. The fMRI response to stimulation frequency was used as an indirect measure of modulation of neuronal activity through pharmacological manipulation. The frequency response to stimulus was attenuated at the lower secondary infusion dosages 100 or 150 μg/kg/hr but not at the higher secondary infusion dosages 200 or 300 μg/kg/hr. Parallel experiments with the animal at rest were carried out using both electroencephalogram (EEG) and functional connectivity MRI (fcMRI) methods with consistent results. In the secondary infusion period using 300 μg/kg/hr, resting-state functional connectivity is enhanced.